2011
DOI: 10.21432/t2nc7b
|View full text |Cite
|
Sign up to set email alerts
|

Digital Learners in Higher Education: Generation is Not the Issue

Abstract: Generation is often used to explain and rationalize the use of information and communication technologies (ICTs) in higher education. However, a comprehensive review of the research and popular literature on the topic and an empirical study at one postsecondary institution in Canada suggest there are no meaningful generational differences in how learners say they use ICTs or their perceived behavioural characteristics. The study also concluded that the post-secondary students at the institution in question use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 9 publications
12
101
0
16
Order By: Relevance
“…However, the assumption that there is a generation of young people -born between 1980 and 1994 -who are characterized by their familiarity and confidence with digital technologies, and who have different learning styles and behavioural characteristics, has been called into question internationally on the basis of rigorous studies by Bennett, Maton and Kervin (2008), Pedró (2009), Brown and Czerniewicz (2010), Corrin, Lockyer and Bennett (2010), Helsper and Eynon (2010), Kennedy, Judd, Dalgarno and Waycott (2010), Bullen, Morgan and Qayyum (2011), Rapetti (2012), and Romero, Guitert, Sangrà and Bullen (2013). Indeed, some of these studies suggest that students of the same age vary greatly in the way they use technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, the assumption that there is a generation of young people -born between 1980 and 1994 -who are characterized by their familiarity and confidence with digital technologies, and who have different learning styles and behavioural characteristics, has been called into question internationally on the basis of rigorous studies by Bennett, Maton and Kervin (2008), Pedró (2009), Brown and Czerniewicz (2010), Corrin, Lockyer and Bennett (2010), Helsper and Eynon (2010), Kennedy, Judd, Dalgarno and Waycott (2010), Bullen, Morgan and Qayyum (2011), Rapetti (2012), and Romero, Guitert, Sangrà and Bullen (2013). Indeed, some of these studies suggest that students of the same age vary greatly in the way they use technology.…”
Section: Introductionmentioning
confidence: 99%
“…During the first analysis and exploration phase at this second university, the DPs were adapted to fit the undergraduate context, and incorporate recent literature. For example, diverse access patterns were noted at the first university, and literature from the period between studying these two contexts, confirmed that students use technology in very diverse ways (Bennett, Maton, & Kervin, 2008;Bullen, Morgan, & Qayyum, 2011;Jelfs & Richardson, 2012;Kennedy, Judd, Churchward, Gray, & Krause, 2008). Consequently, new directions for researching the student transition experience were identified and enriched the EDR process.…”
Section: Applying the Lessons Learnt To A Second Contextmentioning
confidence: 99%
“…are used; blended and web-enhanced learning environments; and independently accessed fully online learning environments Salyers, Carter, Barrett & Williams, 2010). While the literature presents different views on the connection between technology use and how we learn (Bullen, 2011;Bullen, Morgan, & Qayyum, 2011;Tapscott, 2008), today's students use technology more than any generation before them, and there is strong interest among many students in integrating technology with learning. Portable electronic devices and wireless technologies have evolved significantly over the past decade and created drastic changes in our lives (Beckmann, 2010;El-Hussein & Cronje, 2010).…”
Section: Innovation In Contemporary University Education: Trends and mentioning
confidence: 99%